2020
DOI: 10.1021/acsami.9b19075
|View full text |Cite
|
Sign up to set email alerts
|

Toward High-Performance Electron/Hole-Transporting-Layer-Free, Self-Powered CsPbIBr2 Photodetectors via Interfacial Engineering

Abstract: Self-powered photodetectors (PDs) with inorganic lead halide perovskites hold multiple traits of high sensitivity, fast response, independence from external power supply, and excellent sustainability and stability, thus holding a great promise for practical applications. However, they generally contain high-temperature-processed electron-transporting layers (ETLs) and high-cost, unstable hole-transporting layers (HTLs) coupled with noble metal electrodes, which bring significant obstacles of production cost an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…Noting that because of the relatively large work function of FTO, the recombination between extracted electrons in it and holes in CsPbIBr 2 film happens easily, which generally leads to interior performance of the resulting PSC. Our previous study has shown that the introduction of PEI between the FTO and perovskite layer can effectively lower the FTO work function value from 4.52 to 4.25 eV [ 12 ], as also being verified below. Thus, the back-flow of electrons in FTO can be suppressed significantly, and the enhanced performance of the corresponding CsPbIBr 2 PSC can be expected.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…Noting that because of the relatively large work function of FTO, the recombination between extracted electrons in it and holes in CsPbIBr 2 film happens easily, which generally leads to interior performance of the resulting PSC. Our previous study has shown that the introduction of PEI between the FTO and perovskite layer can effectively lower the FTO work function value from 4.52 to 4.25 eV [ 12 ], as also being verified below. Thus, the back-flow of electrons in FTO can be suppressed significantly, and the enhanced performance of the corresponding CsPbIBr 2 PSC can be expected.…”
Section: Resultssupporting
confidence: 62%
“…After the PEI modification (8 mg/mL), the FTO surface potential is obviously improved. A lower work function generally appears with a higher surface potential [ 12 , 27 ]. Therefore, it can be concluded that the work function of FTO has been reduced by the PEI modification, which leads to the more aligned band energies between the work function of FTO and the conduction energy level of CsPbIBr 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[27] Besides, the commonly used electron transport layers, such as TiO 2 , need to be annealed at a relatively high temperature over 400 °C, which is incompatible with most device substrates of flexible photodetectors. [28,29] In addition, the high-performance organic materials based hole transport layer, including spiro-MeOTAD, PTAA, and PEDOT:PSS, are not only deliquescent but also expensive, which are not the appropriate device materials for large-scale fabrication. [30,31] As a result, there is an urgent need to break this bottleneck to achieve a cost-effective scheme to construct the highly-efficient flexible self-powered photodetectors with a simple device configuration.…”
Section: Introductionmentioning
confidence: 99%